Functional Analysis of PARP3 Using Danio rerio as a Vertebrate Animal Model - Gagnon, Abbie (Université d'Ottawa / University of Ottawa, 2012)
PARP1 and PARP2 are the most extensively studied proteins of the poly(ADP-ribose) polymerase (PARP) family. They share partially overlapping functions. These two proteins are best known for their roles in DNA repair. The DNA damage response is actually the most active area of research involving the PARP proteins given the success of PARP inhibitors for cancer therapy. However, PARPs possess many other functions. PARP3, a very little characterized protein, appears to be somewhat involved in the response to DNA damage by genotoxic agents but its physiological function is unknown. Recent evidence indicated that PARP3 is involved in the epigenetic regulation of transcription. For this reason, our collaborators identified PARP3-bound genes by screening the genomic occupancy of PARP3 and found that PARP3-bound genes associate with developmental transcription factors especially involved in neurogenesis. We used zebrafish, a well established vertebrate model in developmental biology, to study the role of PARP3 in development. By knocking-down Parp3 in zebrafish, we found that the loss of Parp3 function reduces the expression of neural crest “specifier” sox9a and of dlx3b/dlx4b. It impairs the formation of cranial sensory placodes, inner ears and pectoral fins. It delays pigmentation and severely impedes the development of the median fin fold and tail bud. In parallel, the reduced expression of Parp3 leads to a massive increase in apoptosis. I also knocked-down Parp1 and Parp2 in zebrafish. Results suggest that the function of Parp1 is different from that of Parp3 in zebrafish while the data from Parp2 were inconclusive. Our findings demonstrate that Parp3 is essential during early stages of zebrafish development, possibly by exerting its transcriptional regulatory functions during the specification of the neural plate border and by mediating cell survival during the early stages of development.
Keywords: parp3; Danio rerio